2020
DOI: 10.3389/fcell.2020.00589
|View full text |Cite
|
Sign up to set email alerts
|

Current Findings Regarding Natural Components With Potential Anti-2019-nCoV Activity

Abstract: COVID-19, a novel coronavirus pneumonia (named by the World Health Organization, WHO), has spread widely since the end of 2019. Research on synthetic drugs and vaccines has become a focus of attention in China and other countries, as such approaches are regarded as key tools for disease prevention and control; however, the development of these therapeutics will take months, or even years. Under such circumstances, development of coronavirus specific therapeutics is urgent. For this specific indication, the rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 100 publications
0
25
0
1
Order By: Relevance
“…Most if not all human beings were caught off guard without suitable defense mechanisms to cope or control such a pandemic. COVID-19, caused by that novel coronavirus species (SARS-CoV-2), has recently been identified and characterized ( Zhou and Huang, 2020 ). Coronaviruses are huge family of viruses that named for their crown-like spikes that found on their surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most if not all human beings were caught off guard without suitable defense mechanisms to cope or control such a pandemic. COVID-19, caused by that novel coronavirus species (SARS-CoV-2), has recently been identified and characterized ( Zhou and Huang, 2020 ). Coronaviruses are huge family of viruses that named for their crown-like spikes that found on their surface.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the causative virus of the current pandemic infected humans through zoonotic transmission ( Saxena, 2020 ; Zimmermann and Curtis, 2020 ). Genetically, SARS-COV-2 is a positive-sense, single stranded RNA virus which encodes for two open reading frames ( Ceraolo and Giorgi, 2020 ; Zhou and Huang, 2020 ). These open reading frames are designated as 1A and 1B.…”
Section: Introductionmentioning
confidence: 99%
“…In SARS-CoV infections, the use of antiviral drugs alone is insufficient for preventing the cytokine storm and related complications in critically ill patients because immune dysregulation in combination with hyperinflammatory conditions leads to complications, worsening the prognosis, rather than addressing viremia [ 36 ]. To reduce COVID-19-related complications and mortality, it is important to identify agents capable of attenuating the cytokine storm, as well as exerting antiviral effects [ 37 ]. In principle, immune responses and the resultant inflammatory process are important for the elimination of the infection; however, they may significantly impact pathogenesis and manifest the clinical spectrum of COVID-19 [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that NPs/SMs are a rich source of drug potential leads against coronaviruses due to their pronounced structural diversity and complexity. Several compilations of pre-2020 findings on NPs/SMs with activity against coronaviruses were recently reported, some of which could serve as leads for the development of new drugs [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Among the identified molecules the majority is represented by NPs ( Figure 2 a) and most of them have been found as inhibitors of SARS-CoV ( Figure 2 b).…”
Section: Nps With Anti-hcov Potentialmentioning
confidence: 99%